The Influence of User Generated Content (UCG) on Skincare Product Purchase Decisions Among Generation Z on TikTok ( A Case Study in Bandung City) - Aflah Malik Alghaniy; Mukaram Mukaram (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study seeks to explore the influence of User Generated Content (UGC) on the purchase decisions of skincare products among Generation Z users on TikTok, using Bandung City as a case study. The research targets individuals from Generation Z who are active TikTok users and reside in Bandung. A purposive sampling technique was used, resulting in a total sample of 155 respondents. Data were collected through a questionnaire distributed via Google Forms to Generation Z users who meet the criteria. The analysis technique used is descriptive analysis and simple linear regression analysis using SPSS software. The findings reveal that User Generated Content (UGC) has a positive and significant effect on the skincare purchase decisions of Generation Z on TikTok, accounting for 40.5% of the variation in purchasing decisions.